2015
DOI: 10.5858/arpa.2015-0361-oa
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing of a Cohort of Pulmonary Large Cell Carcinomas Reclassified by World Health Organization 2015 Criteria

Abstract: The adenocarcinoma with solid pattern group showed mutations typical of adenocarcinoma, whereas the nonkeratinizing squamous cell carcinoma group showed mutations typical of squamous cell carcinoma. Both LCC-N cases had mutations associated with adenocarcinoma, supporting the hypothesis that LCC-N is related to adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
(28 reference statements)
0
21
1
Order By: Relevance
“…Recent mutational analyses of marker-null LCLC cases have suggested that genetic profiling could further reduce the marker-null group beyond IHC scoring by detection of typical adenocarcinoma or SqCC mutations, often favoring an adenocarcinoma lineage. 3,8,14,16 Although recent NGSbased studies 14,16 have reported a notably higher frequency of (especially) adenocarcinoma-linked mutations in marker-null cases than in our cohort, it may be noted that 83% of non-marker-null cases in our marker-nullenriched gene expression cluster (cluster 8) were adenocarcinoma or LCLCs according to the WHO 2004 guidelines that have been reclassified as adenocarcinoma. This observation may lend some support to a hypothesis that marker-null LCLCs represent a variant of undifferentiated TTF1-negative adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Recent mutational analyses of marker-null LCLC cases have suggested that genetic profiling could further reduce the marker-null group beyond IHC scoring by detection of typical adenocarcinoma or SqCC mutations, often favoring an adenocarcinoma lineage. 3,8,14,16 Although recent NGSbased studies 14,16 have reported a notably higher frequency of (especially) adenocarcinoma-linked mutations in marker-null cases than in our cohort, it may be noted that 83% of non-marker-null cases in our marker-nullenriched gene expression cluster (cluster 8) were adenocarcinoma or LCLCs according to the WHO 2004 guidelines that have been reclassified as adenocarcinoma. This observation may lend some support to a hypothesis that marker-null LCLCs represent a variant of undifferentiated TTF1-negative adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 49%
“…The reclassification frequencies observed in the discovery and validation cohorts (70% and 68%, respectively) are consistent with previous studies (59%-90%). 3,14,16,[36][37][38][39][40] Our transcriptional analysis of reclassified WHO 2004 LCLC cases demonstrates that these cases have heterogeneous profiles matching different molecular subsets/GEPs of adenocarcinoma and SqCC, providing additional biological information compared to current diagnostic immunomarkers. Generally, reclassified WHO 2004 LCLCs followed the more aggressive transcriptional phenotypes, such as proximal proliferative or proximal inflammatory in adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Similar ‘doublet’ mutations have been recorded in other genes, such as KRAS in pilocytic astrocytoma or EGFR in lung carcinoma [16,25], but the mechanistic basis of any selective advantage that ‘doublet’ FGFR1 mutations might have is unknown. No FGFR2/3 activating mutations were identified in this study cohort; FGFR2 CNAs were seen, but were rare findings in just 2% of cases.…”
Section: Discussionmentioning
confidence: 75%
“…Tumors with an original diagnosis of large cell carcinoma or NSCLC, not otherwise specified, were reclassified according to 2015 World Health Organization criteria as described in a prior study. 12 Tumors that were reclassified as large cell carcinoma with null immunohistochemical phenotype were excluded from the study.…”
Section: Tissue Microarraysmentioning
confidence: 99%